2019
DOI: 10.22270/jddt.v9i2.2372
|View full text |Cite
|
Sign up to set email alerts
|

Floating Oral In-Situ Gel: A Review

Abstract: The drugs having a narrow absorption window in the gastrointestinal tract (GIT) when administered by oral route are often limited by poor bioavailability due to incomplete drug release and short residence time at the site of absorption. Novel drug delivery systems in the form of gastroretentive systems such as floating systems, mucoadhesive, high-density, expandable have been developed as they provide controlled delivery of drugs with prolonged gastric residence time. Liquid orals are more prone to low bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…In that, in situ gelling systems is a recent development and are versatile across administration routes. Offering advantages such as reduced dosing frequency, good patient compliance, improved bioavailability, cost effective and simple manufacturing process [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that, in situ gelling systems is a recent development and are versatile across administration routes. Offering advantages such as reduced dosing frequency, good patient compliance, improved bioavailability, cost effective and simple manufacturing process [4].…”
Section: Introductionmentioning
confidence: 99%
“…No toxicity was observed with a daily dose of 8 grams of curcumin for three months [3].Researchers performed the investigation on curcumin, and found that curcumin can reduce gastric ulcers by safeguarding the stomach mucus lining and inhibits the growth of ulcer causing organisms. 80 % of gastric ulcer is attributed to antiinflammatory drugs, 10 % of gastric ulcer by food culture and the other 10% by microorganisms [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is typically formulated as its sodium salt Ibandronate sodium. [5][6][7][8][9][10][11][12][13] Ibandronic acid', which suppresses the activity of osteoclasts and makes the bone stronger. Ibandronic acid may reverse bone loss by increasing bone mass and stopping more bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…The in-situ gel-forming drug delivery may be a variety of mucoadhesive drug delivery systems. These gels are liquescent at temperature but submit to gelation in swap body luids in pH [1]. May have a safety feature worldly belongings of room temperature dependant plus cation elicited gelation.…”
Section: Introductionmentioning
confidence: 99%